Electromigration effect upon single- and two-phase Ag-Cu alloy strips: An in situ study. (December 2019) - Liu, Yu-chen; Yu, Yung-si; Lin, Shih-kang; Chiu, Shang-Jui
Abstract: Electromigration (EM) is a major failure mode in electronic interconnections, which is commonly made of Ag, Cu, and their alloys. Herein, a single- and two-phase AgCu alloys were subjected with current density of 4 × 10 5 A/cm 2 for in situ microstructural and crystallographic characterizations. Anomalous grain growth and the formation of cord-like grains with an aspect ratio over 1000 and asymmetrical hillock/voids clusters were found. These abnormal morphological evolutions were resulted from the electron flow-induced lattice strains, which was inversely correlated with the lifespan of interconnection. Multi-phase alloys are less resistant to EM due to the unbalanced electron flow-induced strains. Graphical abstract: Unlabelled Image